การเมือง - ประชาธิปไตย - คอมมิวนิสต์ : การเปลี่ยนแปลงมโนทัศน์ผ่านสายตาของฌอง-ลุค นองซี - กมลกา จิตตรุทธะ (คณะรัฐศาสตร์ มหาวิทยาลัยรามคำแหง, 2022)
Political situations both in Thailand and abroad are the evidence of problem of Democracy. What does this word mean exactly? Some philosophers consider democracy as an empty signifier which has been used for representing any kind of political doctrines so democracy has lost its meaning and does not signify anything after all. This article tried to define the meaning of democracy and communism, which are usually known as an opposition, by referring to Jean-Luc Nancy’s philosophical concepts to clarify and answer three questions as follows: 1) How does politics contaminate with philosophy and democracy? 2) Nancy defines communism as a heart of democracy (as if their meanings are interchangeable). Therefore, the article intends to examine how these terms were transformed and intertwined. The objective of this article is to differentiate three terms: politics, communism and democracy through Nancy’s ontological perspective.